Human milk fat substitute produced by enzymatic interesterification of vegetable oil blend - Karabulut, Ihsan (Array, 2007)
Palm oil, palm kernel oil, olive oil, sunflower oil, and marine oil blend, formulated in the mass ratio of 4.0:3.5:1.0:1.5:0.2, was subjected to interesterification catalyzed by lipase from Thermomyces lanuginosa (Lipozyme® TL IM) for obtaining a product that contains similar triacylglycerol (TAG) structure to that of human milk fat (HMF). Reactions were carried out in a double jacketed glass vessel equipped with magnetic stirrer at 60 °C for 2, 4, 6, 8, 12 and 24 h. The blend was analyzed for fatty acid composition of both total fatty acids and those at the sn-2 position after pancreatic lipase hydrolysis. After interesterification, TAGs were purified by thin layer chromatography and TAG species were determined according to the carbon number (CN) by high-temperature gas chromatography. Enzymatic interesterification generated significant differences for all TAG species from CN30 to CN54. Concentrations of some TAG species (CN30, 32, 34, 36, 38, 50, 52 and 54) decreased, while some (CN40 to 48) increased after 24 h. TAG species with higher CN reached maximum levels at the end of 6 h of reaction time. The predominant TAGs of the reaction product after 24 h were CN46, 48, 50, 52 and 54 with ratios of 13.8, 18.2, 13.9, 17.8, and 12.1 %, respectively. These TAG species contain mainly 1,3-diunsaturated-2-saturated structure, like HMF